Three Dimensional Chemically Reacting Oldroyd-B Fluid + Nanofluid Flow in Presence of Thermophoresis and Brownian Motion Effects - Murali, G.; Deepa, G.; Madhu, J. Venkata; Kasturi, V. Nirmala; Bhati, S.M.; Babu, N. Narendra (Discontinuity, Nonlinearity, and Complexity, 2026)
This paper aims to investigate the impacts of thermal diffusion and diffusion thermo on a steady, viscous, magnetohydrodynamic, incompressible, electrically conducting flow of an Oldroyd-B + nanofluid over a stretched sheet with mixed convection account taken. The study also considers the presence of chemical reactions, Schmidt number, Thermophoresis, Prandtl number, and Brownian motion effects. The current use of similarity variables broadens the scope of application for constitutive equations pertaining to mass, energy, and concentration. The finite element method is used to provide solutions for the given issue of governing equations. The Sherwood number, Nusselt number, and skin-friction coefficients are used to precisely measure the shear stress and the rates of heat and mass transfer at the boundary. Accurate numerical calculations may be accomplished using tables. In order to thoroughly analyze the dynamics of the issue, we conduct a detailed investigation of the tangible impacts of many factors. Afterwards, we use visual methods to emphasize and portray the resulting consequences. In addition, doing a comparison examination of current and previous outcomes provides a more comprehensive understanding of the memory effects.